2020
DOI: 10.1513/annalsats.201907-493oc
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Airway Microbiome and Inflammation with Ivacaftor Treatment in Patients with Cystic Fibrosis and the G551D Mutation

Abstract: Rationale: Modulation of the cystic fibrosis (CF) transmembrane conductance regulator (CFTR) protein improves clinical outcomes in patients with CF and specific CFTR genetic mutations. It remains unclear how improving CFTR function modifies existing airway infection and inflammation.Objectives: To compare sputum microbiome and markers of inflammation before and after 6 months of ivacaftor treatment. Methods:The study included 31 people with CF, ages 10 years and older, with at least one G551D CFTR allele and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 18 publications
(27 reference statements)
3
95
0
Order By: Relevance
“…Second, we performed our analysis at a single time point after treatment, and thus our data capture an early snapshot of acute changes in monocytes after initiation of ivacaftor, which may not reflect chronic therapy. Most studies evaluating changes in cells and biomarkers following initiation of CFTR modulators have sampled subjects at only one time point, with few longitudinal studies ( Rowe et al., 2014 ; Hisert et al., 2017 ; Ronan et al., 2018 ; Kopp et al., 2019 ; Sun et al., 2019 ; Harris et al., 2020 ); however, the synthesis of individual time points with the longitudinal studies suggest that there may be phases of changes in inflammation following restoration of CFTR activity with modulators. The changes reported here occurred within the first week of ivacaftor treatment, and thus reflect acute responses to ivacaftor, and may not reflect a longer term steady-state that incorporates both primary and secondary changes induced by ivacaftor.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we performed our analysis at a single time point after treatment, and thus our data capture an early snapshot of acute changes in monocytes after initiation of ivacaftor, which may not reflect chronic therapy. Most studies evaluating changes in cells and biomarkers following initiation of CFTR modulators have sampled subjects at only one time point, with few longitudinal studies ( Rowe et al., 2014 ; Hisert et al., 2017 ; Ronan et al., 2018 ; Kopp et al., 2019 ; Sun et al., 2019 ; Harris et al., 2020 ); however, the synthesis of individual time points with the longitudinal studies suggest that there may be phases of changes in inflammation following restoration of CFTR activity with modulators. The changes reported here occurred within the first week of ivacaftor treatment, and thus reflect acute responses to ivacaftor, and may not reflect a longer term steady-state that incorporates both primary and secondary changes induced by ivacaftor.…”
Section: Discussionmentioning
confidence: 99%
“…However, early and sustained use of new CFTR modulators may help reverse potential alterations in macrophage inflammatory responses that adversely impact CF outcomes. Prior studies of first-generation CFTR modulators have not shown sustained reductions in sputum inflammatory markers (51,52). New investigations into early immune responses in CF are the focus of several ongoing studies around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that six months of ivacaftor treatment was unable to significantly change airway microbiome and several inflammation measurements in patients carrying at least one G551D mutation. Such findings indicate that antibiotics and anti-inflammatory drugs will still be required to control disease symptoms and prevent complications (Harris et al, 2019). As the disease progresses, patients may also develop comorbidities and thus require even more complex therapeutic regimens, adding further burdens.…”
Section: Continuing the Development Of Transformative Therapeutics Tomentioning
confidence: 99%